Jejunal inflammatory fibroid polyp: a rare cause of intussusception - Talukder, Md Rajibul Haque; Alam, Md Noor A; Uddin, Zahid Iqbal Jamal; Shabnam, Nilufar (Ibrahim Medical College Journal, 2016)
Inflammatory fibroid polyp is a benign and non-neoplastic condition of the gastro-intestinal tract, commonly affecting the gastric antrum, though it can affect any part of the gastro-intestinal tract. It is a submucosal, sessile, polypoid mass composed of myofbroblast like mesenchymal cells, numerous small blood vessels and marked inflammatory cell infiltrate mainly eosinophils. It commonly presents with intestinal obstruction or intussusception. We present here a case of recurrent episodes of small intestinal sub-acute obstruction due to intermittent intussusception associated with inflammatory ûbroid polyp of jejunum. Ibrahim Med. Coll. J. 2015; 9(2): 58-60